Implementing Transparent Financial Governance in Local Neighborhood Association: A Community Engagement Activity - Dema, Yosef; Sismiati; Nurlela; Rudham, Andi Muhammad; Darmawansyah, Iwan; Rahmawan, Rizal (Center for Research and Community Service of Sampoerna University, 2025)
The community service project was undertaken in response to the lack of transparency and accountability in managing community contributions within a neighborhood association in Cipinang Cempedak, Jakarta—particularly those related to cleanliness programs. The activity focused on addressing these issues by promoting clear, accessible, and participatory financial governance at the grassroots level. Appointed as treasurer through Surat Keputusan Lurah Nomor 220 Tahun 2024, the author initiated a monthly reporting system that documented residents' financial commitments and detailed how funds were used. Reports were shared via WhatsApp to enhance accessibility, accountability, and community feedback. This low-cost and inclusive approach fostered financial transparency, strengthened civic engagement, and built trust within the community. The results demonstrate that digital tools and regular reporting can effectively support good governance in local settings. This initiative also reflects the spirit of Pengabdian kepada Masyarakat as part of the Tri Dharma Perguruan Tinggi framework.